ANALISIS KESADARAN MEREK, LOYALITAS PELANGGAN, DAN CITRA MEREK MEMENGARUHI MINAT KONSUMEN UNTUK MEMBELI DI CAFÉ ESTUARY YOGYAKARTA - Aloysius William Pramana; Vincent Loreno Kristiadi; Irra Chrisyanti Dewi (JURNAL ILMIAH EDUNOMIKA, 2026)
This research explores how brand awareness, loyalty, and image influence customers’ willingness to return and make repeat purchases at Café Estuary Yogyakarta. The study was motivated by the growing competition to establish a solid brand identity in order to maintain customer loyalty and encourage recurrent purchases. A data-driven correlational method was used, with data gathered via a Likert-scale questionnaire that was distributed to 200 respondents selected through purposive sampling. The data was subsequently examined through multiple linear regression analysis, supported by tests for validity, reliability, and classical assumptions. The findings reveal that, in general, all the factors significantly impact the intention to repurchase. When examined on its own, brand awareness appears to have little impact (sig. 0.076). On the other hand, both brand loyalty and brand image have a clear and positive influence (sig. 0.000). Furthermore, the R² value of 0.827 indicates that these three factors account for 82.7% of the variation in consumers’ intention to repurchase. These results highlight that while brand awareness alone isn't enough to drive repeat purchases, brand loyalty and brand image are much more influential in shaping consumer behavior. Keywords: brand recognition, customer loyalty, brand perception, the likelihood of repeat purchases